Temporal temperature evolution in laser micro-spot welding of copper considering temperature-dependent material parameters. (27th June 2018) - Mattern, Manuel; Weigel, Thomas; Ostendorf, Andreas
Abstract: One of the main obstacles to the industrial application of laser micro-spot welding of copper is the poor process repeatability at common laser wavelengths. The inhomogeneities in the oxide layer in combination with the high reflectivity of copper itself are often stated as the main reason for the poor repeatability of welding results. However, the typical local variations of the reflectivity alone are not sufficient to describe the instability of the welding process completely. Through numerical FEM simulations, the temperature dependence of the absorptivity could be identified as the main reason for the narrowing of the process window. The effect of the temperature-dependent absorptivity is enhanced by the temperature-dependence of the heat conductivity and slightly reduced by the enthalpy of fusion. The results of the simulation show a good agreement with experimental data.